Synthesis and properties of 5, 7‐disubstituted 5, 7‐dihydropyrido[2, 3‐b:6, 5‐b′]diindoles. Issue 10 (15th March 2017) - Ohlendorf, Lars; Velandia, John E. Diaz; Kónya, Krisztina; Ehlers, Peter; Villinger, Alexander; Langer, Peter
Abstract: A new and efficient two‐step procedure for the preparation of 5, 7‐disubstituted 5, 7‐dihydropyrido[2, 3‐ b :6, 5‐ b ′]diindoles, containing aryl‐, benzyl‐ as well as alkyl‐substituents has been developed. This methodology consists of a chemo‐selective double Suzuki‐Miyaura cross‐coupling reaction followed by a fourfold Buchwald‐Hartwig amination reaction. UV/VIS absorption and fluorescence measurements have been carried out for a selected series of compounds. The results are summarized and compared with those of the isomeric 5, 7‐disubstituted 5‐7‐dihydropyrido[3, 2‐ b :5, 6‐ b ′]diindoles. Abstract :